Determinants of Tax Morale: Cross-sectional Evidence from African Survey Data: Array - Nyamapheni, Joseph; Robinson, Zurika (The Journal of Accounting and Management, 2021)
Objectives: The article becomes novel in that it provides a comparative analysis of the determinants of the tax morale between South Africa and Zimbabwe as neighbouring countries. Design/methodology: Prior work: Research has shown that tax morale in African countries is generally lower than it is in developed and transition countries. Approach: The article was guided by quantitative research which was used to inform the study. Data was collected using questionnaires from the 2010-2014 and 2017-2020 World Values Survey (WVS). For Zimbabwe, Wave 6 and Wave 7 had a sample size of 1500 and 1200 respectively. Findings: The study concludes with an understanding of how tax morale and its determinants is crucial for governments in their bid to boost voluntary compliance. Surprisingly, the study’s results showed that Zimbabweans have a higher tax morale than South Africans, who have better standards of living. In addition, the determinants of tax morale also differ from one economic situation to another and from one country to another. Corruption, which is a menace in both countries under study, has proven to be an important factor that influences tax morale. Results of all the models show that demographic factors have little effect on tax morale. Value: The study introduced an important variable of hunger in its analysis of determinants of tax morale. Though this variable was insignificant for South Africa, the study showed that there is a negative relationship between hunger and tax morale for Zimbabwe in both economic situations. Implications: Policy makers should consider the eradication of corruption and hunger in order to boost tax morale, which in turn improves tax compliance. Continued tax education and the improvement of the perception on democracy should be included in the mix of tax compliance enhancement strategies.